2015
DOI: 10.1186/s12885-015-1550-0
|View full text |Cite
|
Sign up to set email alerts
|

GTSE1 expression represses apoptotic signaling and confers cisplatin resistance in gastric cancer cells

Abstract: BackgroundPlatinum based therapy is commonly used in the treatment of advanced gastric cancer. However, resistance to chemotherapy is a major challenge that causes marked variation in individual response rate and survival rate. In this study, we aimed to identify the expression of GTSE1 and its correlation with cisplatin resistance in gastric cancer cells.MethodsMethylation profiling was carried out in tissue samples from gastric cancer patients before undergoing neoadjuvent therapy using docetaxel, cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…Genes with a degree of connection exceeding 15, except for SPAG5 , have been previously linked to the development of gastric cancer. 33 , 34 , 35 , 36 , 37 The result demonstrates the robustness of our bioinformatics analysis methods and reveals a gastric cancer-promoting interaction network associated with cyclin E.…”
Section: Discussionmentioning
confidence: 57%
“…Genes with a degree of connection exceeding 15, except for SPAG5 , have been previously linked to the development of gastric cancer. 33 , 34 , 35 , 36 , 37 The result demonstrates the robustness of our bioinformatics analysis methods and reveals a gastric cancer-promoting interaction network associated with cyclin E.…”
Section: Discussionmentioning
confidence: 57%
“…Emerging evidence indicated abnormal expression of genes in cell cycle, and apoptosis regulation, like p53, Rb, p27, and TGFβ/IGF2R, is related to etiopathogenesis and prognosis of liver cancer patients [1]. GTSE1 has been demonstrated as a potential biomarker for poor clinical outcome in several types of cancer [10,13,27]. Previous research suggested GTSE1's functional role in hepatocellular carcinoma (HCC) proliferation, colony formation, invasion, and overall survival [9,13].…”
Section: Discussionmentioning
confidence: 99%
“…GTSE1 accumulates in the nucleus and binds to p53, resulting in its translocation out of the nucleus and suppression of its apoptosis-inducing ability. In addition, GTSE1 suppresses apoptotic signaling and confers cisplatin resistance in gastric cancer cells (20). Overexpression of GTSE1 has previously been observed in KIRC (21) and may therefore exert a similar function in KIRC.…”
Section: Discussionmentioning
confidence: 99%